Chaperonin-mediated protein folding: using a central cavity to kinetically assist polypeptide chain folding - Horwich, Arthur L.; Fenton, Wayne A. (Quarterly reviews of biophysics, 2009)
The chaperonin ring assembly GroEL provides kinetic assistance to protein folding in the cell by binding non-native protein in the hydrophobic central cavity of an open ring and subsequently, upon binding ATP and the co-chaperonin GroES to the same ring, releasing polypeptide into a now hydrophilic encapsulated cavity where productive folding occurs in isolation. The fate of polypeptide during binding, encapsulation, and folding in the chamber has been the subject of recent experimental studies and is reviewed and considered here. We conclude that GroEL, in general, behaves passively with respect to its substrate proteins during these steps. While binding appears to be able to rescue non-native polypeptides from kinetic traps, such rescue is most likely exerted at the level of maximizing hydrophobic contact, effecting alteration of the topology of weakly structured states. Encapsulation does not appear to involve ‘forced unfolding’, and if anything, polypeptide topology is compacted during this step. Finally, chamber-mediated folding appears to resemble folding in solution, except that major kinetic complications of multimolecular association are prevented.